Nuclear organization in crucifer genomes: nucleolus-associated telomere clustering is not a universal interphase configuration in Brassicaceae - Shan, Wenbo; Kubová, Michaela; Mandáková, Terezie; Lysak, Martin A (The Plant journal, 2021)
Arabidopsis thaliana has become a major plant research model, where interphase nuclear organization exhibits unique features, including nucleolus-associated telomere clustering. The chromocenter (CC)-loop model, or rosette-like configuration, describes intranuclear chromatin organization in Arabidopsis as megabase-long loops anchored in, and emanating from, peripherally positioned CCs, with those containing telomeres associating with the nucleolus. To investigate whether the CC-loop organization is universal across the mustard family (crucifers), the nuclear distributions of centromeres, telomeres and nucleoli were analyzed by fluorescence in situ hybridization in seven diploid species (2n = 10-16) representing major crucifer clades with an up to 26-fold variation in genome size (160-4260 Mb). Nucleolus-associated telomere clustering was confirmed in Arabidopsis (157 Mb) and was newly identified as the major nuclear phenotype in other species with a small genome (215-381 Mb). In large-genome species (2611-4264 Mb), centromeres and telomeres adopted a Rabl-like configuration or dispersed distribution in the nuclear interior; telomeres only rarely associated with the nucleolus. In Arabis cypria (381 Mb) and Bunias orientalis (2611 Mb), tissue-specific patterns deviating from the major nuclear phenotypes were observed in anther and stem tissues, respectively. The rosette-like configuration, including nucleolus-associated telomere clustering in small-genome species from different infrafamiliar clades, suggests that genomic properties rather than phylogenetic position determine the interphase nuclear organization. Our data suggest that nuclear genome size, average chromosome size and degree of longitudinal chromosome compartmentalization affect interphase chromosome organization in crucifer genomes.
Keywords: Crucifereae; chromocenter-loop model; ribozomální DNA; Arabidopsis; Interphase; In Situ Hybridization, Fluorescence; Centromere; Chromatin; Arabis; telomere; Rabl; telomery; Cell Nucleolus; Brassicaceae; centromere; chromatin; Heterochromatin; fylogeneze; DNA, Ribosomal; nucleolus; hybridizace in situ fluorescenční; centromera; Genome Size; buněčné jadérko; Telomere; interphase; heterochromatin; genom rostlinný; Genome, Plant; Phylogeny; interfáze; Arabidopsis thaliana; délka genomu